Tertiary lymphoid structures in colorectal cancer - Jianyu Lv; Xiuyu Zhang; Mi Zhou; Junbin Yan; Guanqun Chao; Shuo Zhang (Annals of Medicine)
Background Tertiary lymphoid structures (TLS) are ectopic clusters of immune cells found in non-lymphoid tissues, particularly within the tumor microenvironment (TME). These structures resemble secondary lymphoid organs and have been identified in various solid tumors, including colorectal cancer (CRC), where they are associated with favorable prognosis. The role of TLS in modulating the immune response within the TME and their impact on cancer prognosis has garnered increasing attention in recent years.Objective This review aims to summarize the current understanding of TLS in CRC, focusing on their formation, function, and potential as prognostic markers and therapeutic targets. We explore the mechanisms by which TLS influence the immune response within the TME and their correlation with clinical outcomes in CRC patients.Methods We conducted a comprehensive review of recent studies that investigated the presence and role of TLS in CRC. The review includes data from histopathological analyses, immunohistochemical studies, and clinical trials, examining the association between TLS density, composition, and CRC prognosis. Additionally, we explored emerging therapeutic strategies targeting TLS formation and function within the TME.Results The presence of TLS in CRC is generally associated with an improved prognosis, particularly in early-stage disease. TLS formation is driven by chronic inflammation and is characterized by the organization of B and T cell zones, high endothelial venules (HEVs), and follicular dendritic cells (FDCs). The density and maturity of TLS are linked to better patient outcomes, including reduced recurrence rates and increased survival. Furthermore, the interplay between TLS and immune checkpoint inhibitors (ICIs) suggests potential therapeutic implications for enhancing anti-tumor immunity in CRC.Conclusions TLS represent a significant prognostic marker in CRC, with their presence correlating with favorable clinical outcomes. Ongoing research is required to fully understand the mechanisms by which TLS modulate the immune response within the TME and to develop effective therapies that harness their potential. The integration of TLS-focused strategies in CRC treatment could lead to improved patient management and outcomes.